2011
DOI: 10.1093/ecam/nen049
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Mutagenic Activity of Extracts of Brazilian Propolis in Topical Pharmaceutical Formulations on Mammalian Cells In Vitro and In Vivo

Abstract: Propolis possesses various biological activities such as antibacterial, antifungal, anti-inflammatory, anesthetic and antioxidant properties. A topically applied product based on Brazilian green propolis was developed for the treatment of burns. For such substance to be used more safely in future clinical applications, the present study evaluated the mutagenic potential of topical formulations supplemented with green propolis extract (1.2, 2.4 and 3.6%) based on the analysis of chromosomal aberrations and of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Previous studies in vitro and in vivo models have demonstrated the absence of cytotoxic and mutagenic potential of propolis gel [12, 22]. Based on these previous studies, the composition used in the present study was determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in vitro and in vivo models have demonstrated the absence of cytotoxic and mutagenic potential of propolis gel [12, 22]. Based on these previous studies, the composition used in the present study was determined.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the safety of standardized extract of propolis (EPP-AF) has been demonstrated, showing that it is a noncytotoxic product and has no mutagenic potential with either oral or topic use [12, 13]. Moreover, EPP-AF has anti-inflammatory [13, 14], antiulcer [15], wound healing, antimicrobial [16, 17], and fungicidal activities [11, 1821].…”
Section: Introductionmentioning
confidence: 99%
“…The external use of propolis is defined by the application of pharmaceutical or natural products on the surface or point of illness [ 23 ]. External uses of propolis (EUP) include the use of pharmaceutical, cosmetic, and oral products such as ointment [ 24 ], gel [ 25 ], and mouthwash [ 26 ].…”
Section: Propolis In the Treatment Of Oral Mucositismentioning
confidence: 99%
“…Currently, more than 300 compounds, such as phenolic acid, terpenes, cinnamic acid, caffeic acid, several esters, and flavonoids have been identified as constituents of propolis from different geographic origins (Senedese et al, 2011;Huang et al, 2014). Propolis exerts numerous pharmacological benefits such as antioxidant, antibacterial, antiviral, antitumor, anti-inflammatory, anticancer and immunomodulatory activities (Basim et al, 2006;Kaewmuangmoon et al, 2012;Hongzhuan et al, 2014).…”
mentioning
confidence: 99%